Retinal revascularisation in diabetic retinopathy. Issue 2 (February 1986) - Mohan, R; Kohner, E M
Abstract : The case history of a 33-year-old diabetic patient who has had diabetes for 24 years is presented. When first seen in 1975 he had bilateral proliferative retinopathy with new vessels in the retinal periphery. He had large areas of capillary non-perfusion lateral to the macula in the right eye associated with the new vessels. Nine years later, after extensive repeated photocoagulation, revascularisation of large areas previously not perfused were seen. The vessels are in the plane of the retina and do not have the appearance of new vessels.